Correlation Assessment of unstimulated whole saliva flow rate with anthropometric indices - Maryam Rabiei; Mohsen Maddah; Maryam Ghamgosar (Islamic Dental Association of Iran, 2016)
Background and Aim: Controversy exists regarding the correlation of saliva secretion with obesity. Considering the significant role of saliva in oral and dental health and the increasing prevalence of obesity in Iran in the past three decades, this study aimed to assess the independent association of anthropometric indices including body mass index (BMI), weight gain after the age of 20 years and waist circumference (WC) with unstimulated whole saliva flow rate. Materials and Methods: This comparative cross-sectional study was conducted on 313 systematically healthy subjects who referred to Guilan Dental School. Age, gender, the level of education, BMI, WC and weight gain after the age of 20 was recorded. Unstimulated whole saliva flow rate was measured and the independent association of anthropometric indices with saliva flow rate was statistically analyzed. Statistical significance was set at P < 0.05. Results: 331 subjects (186 females and 145 males) were evaluated. Among them, 107 were obese (BMI≥30kg/m2), 114 were overweight (BMI=25-29.9kg/m2), and 110 had normal weight (BMI=18.5-24.9kg/m2). The mean saliva flow rate was 0.33ml/minute. The odds ratio of reduction in saliva flow below the mean value (0.33mL/minute) in obese compared to normal weight individuals was 1.84. The cut-off point of saliva flow reduction was 10.20 kg weight gain after the age of 20 with 62.3% sensitivity and 61.2% specificity. Weight gain after the age of 20 (odds ratio=1.06, 95% CI: 1.03-1.08) and gender (odds ratio: 1.87, 95% CI: 1.18-2.97) were found to be predictors of saliva flow reduction. Conclusion: This study showed that weight gain in adults was significantly correlated with the saliva flow rate, and weight gain after the age of 20 years was the main anthropometric index related to saliva flow reduction. The mean saliva flow rate in overweight and obese females was higher than counterpart males. Key Words: Weight Gain, Saliva, Body Mass Index, Obesity